Determinants of cocoa farmer’s participation in the innovation platform of the humidtropics programme in Southwestern Nigeria - Akinmusola, O.; Soyebo, K.O.; Farinde, A.J.; Amujoyegbe, B.J.; Idrissou, L.; Gaya, H.; Fatunbi, O.; Ilesanmi, R.Y. (2016)
In an effort to determine factors influencing cocoa farmer’s participation in innovation platform (IP) activities of the Humidtropics programme, data was collected from purposively selected 177 farmers using multistage technique sampling technique and was gathered through the use of structured interview schedule. Data were collected and analyzed with percentage, frequency counts, mean, standard deviation and factor analysis. The study shows the mean age of the cocoa farmers in the IP to be 51.16±12.64 with about 52% aged above 50 years, female were only (23.73%), with more than 75th percentile literacy level and only about 31% of respondents generate annual income from farming above ₦50,000 while about 70% made below ₦40,000 extra income from other occupation. The mean farm size was 16.87 ±16.04 acre, farming experience 25.42±10.48 years and household size was 9.78±5.52. The six significant determinants of cocoa farmer’s participation in IP arranged in order of magnitude are psychological factor (λ = 3.158), experience factor (λ = 2.164), community related factor (λ = 1.697) educational factor (λ = 1.854), economic factor (λ =1.438) and internal factor (λ = 1.113). The summative effect of the identified factors accounted for 76.17 % variation observed in cocoa farmer’s participation in the IP.